Polysaccharide Extracted from Laminaria japonica Delays Intrinsic Skin Aging in Mice. (6th April 2016) - Hu, Longyuan; Tan, Jia; Yang, Xiaomei; Tan, Haitao; Xu, Xiaozhen; You, Manhang; Qin, Wu; Huang, Liangzhao; Li, Siqi; Mo, Manqiu; Wei, Huifen; Li, Jing; et al.
Abstract : This study aimed to determine the effect of topically applied Laminaria polysaccharide (LP) on skin aging. We applied ointment containing LP (10, 25, and 50  μ g/g) or vitamin E (10  μ g/g) to the dorsal skin of aging mice for 12 months and young control mice for 4 weeks. Electron microscopy analysis of skin samples revealed that LP increased dermal thickness and skin collagen content. Tissue inhibitor of metalloprotease- (TIMP-) 1 expression was upregulated while that of matrix metalloproteinase- (MMP-) 1 was downregulated in skin tissue of LP-treated as compared to untreated aging mice. Additionally, phosphorylation of c-Jun N-terminal kinase (JNK) and p38 was higher in aging skin than in young skin, while LP treatment suppressed phospho-JNK expression. LP application also enhanced the expression of antioxidative enzymes in skin tissue, causing a decrease in malondialdehyde levels and increases in superoxide dismutase, catalase, and glutathione peroxidase levels relative to those in untreated aging mice. These results indicate that LP inhibits MMP-1 expression by preventing oxidative stress and JNK phosphorylation, thereby delaying skin collagen breakdown during aging.